2019
DOI: 10.3390/jcm8050589
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Systemic Inflammatory Indices, NLR, PLR, and MPV, for Predicting 1-Year Survival of Patients Undergoing Cytoreductive Surgery with HIPEC

Abstract: The neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and mean platelet volume (MPV) have been reported to be associated with the prognosis of various types of tumors. This study evaluated the prognostic value and clinical use of inflammatory markers for predicting 1-year survival in patients undergoing cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC). This retrospective study included 160 patients who underwent CRS with HIPEC between July 2014 and Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 37 publications
0
26
0
1
Order By: Relevance
“…Recent literature has shown that some components of the routine complete blood cell (CBC) count, such as white blood cell count (WBC), hemoglobin, neutrophil count, lymphocyte count, platelet count, red cell distribution width (RDW), mean platelet volume (MPV), and some of their ratios, such as neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR), can aid in the diagnosis of malignancies, cardiovascular disease, autoimmune diseases, and some pregnancy pathologies [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature has shown that some components of the routine complete blood cell (CBC) count, such as white blood cell count (WBC), hemoglobin, neutrophil count, lymphocyte count, platelet count, red cell distribution width (RDW), mean platelet volume (MPV), and some of their ratios, such as neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR), can aid in the diagnosis of malignancies, cardiovascular disease, autoimmune diseases, and some pregnancy pathologies [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 , 20 ] This suggests that the peripheral blood immune responses can be used as prognostic factors for acute brain injuries. NLR, PLR, and MPV are known to be associated with inflammation, [ 9 , 11 , 21 ] and NLR has been investigated as a prognostic factor for TBI and other neurosurgical emergencies. [ 3 , 16 , 22 ] Therefore, we investigated the association between hematologic parameters, including inflammatory indices, and mortality among EDH or SDH patients undergoing emergency surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Posttraumatic neuroinflammation is a secondary injury after trauma that causes neurodegeneration and neurological impairment. [ 4 8 ] The associations between poor prognoses in various types of cancer and inflammatory mediators have been well documented [ 9 11 ] ; additionally, acute TBIs and inflammation are known to be associated. [ 12 14 ] Recent studies have suggested that increased levels of inflammatory markers are the predictors of worse outcomes in acute neurosurgical emergencies, such as TBI, intracerebral hemorrhage (ICH), and subarachnoid hemorrhage (SAH).…”
Section: Introductionmentioning
confidence: 99%
“…Серед інших показників важливо відмітити що крім PLR та NLR, які у більшості випадків підтвердженої інфекції Sars CoV-2 більш тонким показником виявився показник індексу системної реакції запалення (SIRI = відношення нейтрофілів x моноцитів / лімфоцитів) [8,14]. При надходженні даний показник самостійно прогнозує внутрішньолікарняну смертність у пацієнтів з COVID-19 і може допомогти ранньої стратифікації ризику у цій групі [17].…”
Section: результатиunclassified